YIELD AND QUALITY PARAMETERS OF WINTER AND SUMMER-SOWN DIFFERENT CAMELINA (Camelina sativa L.) GENOTYPES - Kinay, Ahmet; Yilmaz, Gungor; Ayisigi, Samet; Dokulen, Saziye (Soc Field Crop Sci, 2019)
The present study was conducted to determine the performance of summer and winter-sown camelina lines in 2013-2014 and 2014-2015 growing seasons. In experiments, 11 camelina genotypes (Vinimik 17, PI304269, CR 476/65, CR 1674/90, Ames 26665, Ames 26667, Ames 26673, Ames 26676, Ames 26680, Ames 26686 and Ames 28372) were used as the plant materials. Plant height, number of pod per plant, number of seeds per pod, thousand-seed weight, seed yield, oil ratio and oil yield values were measured. The differences in investigated traits of the genotypes were found to be significant (p<0.05). Winter sowings had better performance than summer sowings for yield and yield components. Winter-sown camelina plants were harvested at the end of May or at the beginning of June, which means that it is a good pre-plant for camelina. Average seed yields varied between 2.127 - 4.943 ton ha(-1) in winter sowings and between 0.582 - 4.609 ton ha(-1) in summer sowings; oil ratios varied respectively between 32.1 - 33.4% and between 24.3 - 35.1%. It was concluded based on findings that camelina should be produced as winter-sown with Ames-26686 genotype. Furthermore, Ames26680, Ames-26686 and Ames 28372 genotypes could also be grown as summer-sown with quite reliable performance levels in years with sufficient spring precipitations.
Keywords: Oil ratio; oil yield; seed yield; summer sowing; winter sowing